(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article explores the etymological characteristics of Latin borrowings in Modern English, shedding light on the enduring impact of Latin on the English language. Through a comprehensive analysis of literature and linguistic data, this study aims to uncover patterns, trends, and transformations in Latin loanwords, tracing their journey from classical origins to their assimilation into the contemporary lezicon.